The effect of lower extremity fatigue on shock attenuation during landing - O`Connor, K. M.; Coventry, E.; Hart, B. A.; Monteiro, S. K.; Earl, J. E.; Ebersole, K. T. (ISB Congress, 2005)
The purpose of the study was to determine the effect of lower extremity fatigue on shock attenuation and joint mechanics during a drop landing. It was hypothesized that lower extremity fatigue would cause a decrease in the shock attenuation and alter joint mechanics. The results suggested that the lower extremity is able to adapt to fatigue though altering kinematics at impact and redistributing work to larger proximal muscles.